Balaghah Analysis of the Tashbih Sentences in the Book of Al-Lubab Al-Hadith: Analisis Balaghah pada Kalimat Tasybih dalam Kitab Al-Lubab Al-Hadits - Azis, Moch Cecep Abdul (Institut Agama Islam Negeri Kerinci, 2024)
Tasybih is lexically a simile. While terminologically tasybih is likening or equating one thing with another because of the similarity in one or several characteristics in a meaning by using tasybih instruments or what is called Adat Tasybih. This study analyzes and understands the types of tasybih and the purpose of tasybih contained in Al-Lubab Al-Hadith. This study aims to describe the types and purposes of tasybih in Al-Lubab Al-Hadith. So that it can be known what types of tasybih are contained in the book of Al-Lubab Al-Hadith and the purpose of tasybih. This study uses analytic descriptive method. The data collection technique in this study uses literature study technique, because the data in this study is qualitative data. Thus, the method used in this study is to reveal and explain the types of tasybih and the purpose of tasybih in the book of Al-Lubab Al-Hadith. While the approach adopted in this study is the science of bayan, namely tasybih. Based on the results of the study of Al-Lubab Al-Hadith, the types of tasybih contained in Al-Lubab Al-Hadith consist of 12 types of mursal tasybih, 12 mujmal tasybih. Then the purpose of tasybih sentences contained in the book Al-Lubab Al-Hadith consists of 9 bayan hal al-musyabbah and 3 bayan imkan al-musyabbah.